2017
DOI: 10.1002/mren.201700051
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preparation of Highly Filled Water‐Borne Polymer–Gibbsite Nanocomposites

Abstract: The discovery of a reversible additionfragmentation chain transfer (RAFT)-mediated encapsulation method for filler materials, [12] however, caused a significant shift in encapsulation strategy and many examples now exist in which this method was applied successfully. [13][14][15][16][17][18][19][20] We recently extended this method to an atom transfer radical polymerization (ATRP)-based method, [21] which only in the presence of a cross-linker led to encapsulated particles; [22] without cross-linker so-called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…[4][5][6][7][8] The preparation of randomly orientated montmorillonite nanocomposite films, prepared by emulsion polymerization, has been reported to enhance oxygen barrier properties by only 30.3% at 1 wt% concentration, thus highlighting the need to develop methods that allow for simultaneous control over orientation and exfoliation. 9 Control over the orientation of nanofiller has been achieved using emulsion polymerization by Heuts et al, who demonstrated the encapsulation of both natural (montmorillonite) [10][11] and synthetic (gibbsite) [12][13][14][15] clays. Using atom transfer radical polymerization (ATRP) and reversible addition-fragmentation chain-transfer (RAFT) polymerization they prepared co-oligomers, which function as both the nanoparticle stabilizer and as a macro-initiator or macro-chain transfer agent for polymer chain extension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] The preparation of randomly orientated montmorillonite nanocomposite films, prepared by emulsion polymerization, has been reported to enhance oxygen barrier properties by only 30.3% at 1 wt% concentration, thus highlighting the need to develop methods that allow for simultaneous control over orientation and exfoliation. 9 Control over the orientation of nanofiller has been achieved using emulsion polymerization by Heuts et al, who demonstrated the encapsulation of both natural (montmorillonite) [10][11] and synthetic (gibbsite) [12][13][14][15] clays. Using atom transfer radical polymerization (ATRP) and reversible addition-fragmentation chain-transfer (RAFT) polymerization they prepared co-oligomers, which function as both the nanoparticle stabilizer and as a macro-initiator or macro-chain transfer agent for polymer chain extension.…”
Section: Introductionmentioning
confidence: 99%
“…Control over the orientation of nanofiller has been achieved by using emulsion polymerization by Heuts et al, who demonstrated the encapsulation of both natural (montmorillonite) , and synthetic (gibbsite) clays. Using atom transfer radical polymerization (ATRP) and reversible addition–fragmentation chain-transfer (RAFT) polymerization, they prepared co-oligomers, which function as both the nanoparticle stabilizer and as a macroinitiator or macro-chain-transfer agent for polymer chain extension. Control over the particle morphology was reported via RAFT under starved fed conditions, where the clay sheets act as seeds for polymerization, forming anisotropic particles that align the nanoplatelets against the substrate in the cast film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation